1999
DOI: 10.1523/jneurosci.19-20-08757.1999
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Analysis of GluR5(Q636R) Kainate Receptor Mutant Mice

Abstract: The physiological significance of RNA editing of transcripts that code for kainate-preferring glutamate receptor subunits is unknown, despite the fact that the functional consequences of this molecular modification have been well characterized in cloned receptor subunits. RNA editing of the codon that encodes the glutamine/arginine (Q/R) site in the second membrane domain (MD2) of glutamate receptor 5 (GluR5) and GluR6 kainate receptor subunits produces receptors with reduced calcium permeabilities and single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 54 publications
2
35
0
1
Order By: Relevance
“…The results presented here agree with a previous study that used a selective GluR5 antagonist, LY382884, to show that inhibition of GluR5 activity reduces behavioral responses to formalin (Simmons et al, 1998). Another study showed that mice bearing a targeted mutation at a critical RNA editing site of the GluR5 gene had normal responses to formalin (Sailer et al, 1999). The reason for this discrepancy may be attributable to different levels of functional GluR5 receptors between this transgenic mouse and the ones used here, because the RNA editing mutant retains some functional receptors.…”
Section: Kars: Nociception and Inflammatory Painsupporting
confidence: 91%
“…The results presented here agree with a previous study that used a selective GluR5 antagonist, LY382884, to show that inhibition of GluR5 activity reduces behavioral responses to formalin (Simmons et al, 1998). Another study showed that mice bearing a targeted mutation at a critical RNA editing site of the GluR5 gene had normal responses to formalin (Sailer et al, 1999). The reason for this discrepancy may be attributable to different levels of functional GluR5 receptors between this transgenic mouse and the ones used here, because the RNA editing mutant retains some functional receptors.…”
Section: Kars: Nociception and Inflammatory Painsupporting
confidence: 91%
“…These data are in agreement with other studies conducted in GluR5 KO maintained on a mixed 129 ϫ C57BL/6 background (Ko et al, 2005) or in GluR5(Q636R) editing mutants (Sailer et al, 1999), which found no difference from WT mice with respect to mechanical or thermal thresholds. The lack of involvement of GluR5 in baseline nociceptive sensitivity is further supported by the finding that acute morphine antinociception (ED 50 value, Table 1) is not different between WT and GluR5 KO.…”
Section: Discussionsupporting
confidence: 93%
“…A value of p Ͻ 0.05 was considered significant. (Sailer et al, 1999). First, we examined the development of antinociceptive tolerance in WT and GluR5 KO mice after repeated subcutaneous injections of morphine.…”
Section: Glur5 Knockout Attenuates Morphine Tolerance 581mentioning
confidence: 99%
“…However, a role of Q/R site editing of AMPA or kainate receptors suggested by murine models (Sailer et al, 1999;Vissel et al, 2001; this study) remains speculative and has been neither confirmed nor refuted by recent investigations into the editing status of GluR transcripts in brain tissue excised from patients with temporal lobe epilepsy (Grigorenko et al, 1998;Kortenbruck et al, 2001). …”
Section: Introductionmentioning
confidence: 70%